Cutis marmorata telangiectatica congenita - El Fekih, N.; Hafsi, W.; Zine, N.; Marrakchi, Z.; Fazaa, B. (European Journal of Pediatric Dermatology, 2012)
A 1-day-old female infant was referred to our service for evaluation of reticulate cutaneous lesions of the trunk and limbs, which were present since birth. On physical examination, a blue-violet reticulate skin pattern with areas of macular erythema and telangiectasias was present in the trunk, upper and lower extremities, particularly in the left part of the body (Fig. 1). The lesions blanched with pressure and worsened with crying. There were also areas of atrophy on the right knee (Fig. 2) and left ankle without ulceration. Neither asymmetry of the limbs no any other cutaneous anomaly was noted. The examination of the other organs showed no abnormalities. The final diagnosis was cutis marmorata telangiectatica congenita. Abdominal and trans-fontanel ultrasonographies showed no abnormality. Two months later on a control examination the lesions were less evident.